PSYCHOLOGICAL FEATURES OF THE MANIFESTATION OF REFLEXIVITY IN ADOLESCENCE - D. E. Yulchiboeva (Galaxy International Interdisciplinary Research Journal, 2023)
The article outlines the role and significance of psychological factors affecting the manifestation of reflexivity in adolescence. Analysis of the research of foreign scientists on adolescent reflexivity has also been described. In particular, the features of the manifestation of reflexivity in adolescence have been studied on the basis of empirical studies.